Improving the Deployment of Army Health Care Professionals An Evaluation of PROFIS - Sorbero, Melony E. (RAND Corporation, 2013)
The Army Medical Department uses the Professional Filler System (PROFIS) to manage the deployment of health care professionals and their assignment to military treatment facilities when not deployed. This report describes the functionality of PROFIS in the current operating environment of ongoing deployments and assesses potential modifications and improvements to the system.